When do ruling elites support productive sectors? Explaining policy initiatives in the fisheries and dairy sectors in Uganda - Anne Mette Kjær; Mesharch Katusiimeh; Tom Mwebaze; Fred Muhumuza (Danish Institute for International Studies (DIIS), 2012)
This paper explains the differences in ruling elite support for the fisheries and dairy sectors in Uganda. Although production in Uganda has not generally been promoted in any sustained way, ruling elites have to varying degrees supported the dairy and fisheries sectors. The paper shows that the ruling elite initially supported the fishing industry because of industry pressure. They have failed to enforce fisheries management because there are big political costs associated with such enforcement. The dairy sector in the southwestern milk region was initially supported because the ruling elite wanted to build a coalition of support in this region. Coming from the region himself, the president had a keen interest in dairy cattle. The sector was subsequently regulated because the biggest processor put pressure on the ruling elite to do so. Even when the ruling coalition is fragmented, promoting production is possible if there is strong industry pressure and when the initiatives to promote the sector are also seen to help build or maintain the ruling coalition.
Keywords: 300; Fischereipolitik; Milchviehhaltung; Milchverarbeitung; Patronage; Uganda